Red urine syndrome in dromedary camels: Clinical, etiological, hematobiochemical sonographic and pathologic findings - Mohamed Tharwat; Hazem MM Elmoghazy; Ayman Swelum; Tariq I. Almundarij (Open Veterinary Journal, 2024)
Background: Although blood urine is frequently observed in dromedary camels, little attention is gained and only it was reported as case reports. Aim: This study was carried out to examine dromedary camels suffering from red urine syndrome from the points of the clinical, etiological, hematobiochemical, ultrasonographic and pathological characteristics. Methods: Thirty-one camels with red urine and fifteen controls were enrolled. With a duration ranging from five days to nine months, clinical manifestations included weakness, red discoloration of the urine, dribbling of urine, straining during urination and abdominal pain. Blood was sampled in EDTA and plain tubes. Results: The urine red color intensity was marked in 23 camels. In 5 camels discolored red urine was moderate while red urine was voided intermittently in the remaining 3 camels. Wide stance of the hind legs and pain reactions during urination were recorded in 18 camels. In all 31 camels, urine samples were centrifuged and sedimentation of red deposits was found. Nephrolithiasis was detected in 3 animals. one female camel had bilateral hydronephrosis. Hyperechoic urine was imaged within the renal pelvis in 7 camels. In addition, hypoechoic fluid was imaged within the peritoneal cavity in 8 animals. Ruptured and collapsed urinary bladder was found in 2 male camels. In addition, bilateral pyelonephritis was found in another male camel. Abscessation of the left and right kidneys confirmed by ultrasound-guided aspiration was confirmed in 3 and 2 females, respectively. Peri-renal abscessation of the right kidney was detected in a female camel. Large, misshaped hypoechoic mass involving the right kidney was found in 1 female. A large mass king neoplasia was also imaged in a female camel distal to and compressing the left kidney, which proved histologically to be leiomyoma. Moderate to severe thickening and corrugation of the urinary bladder mucosa was detected in 18 of the diseased camels. Conclusion: This study's syndrome of red urine in camels resulted mainly from hematuria. The existing etiologies were the nephrolithiasis, cystitis, pyelonephritis, peri-renal and renal abscessation, and renal neoplasia. Ultrasonography was superior in assessing the renal parenchyma and urinary bladder for the verification of the existing nephrolithiasis, hydronephrosis, pyelonephritis, peri-renal and renal abscessation, cystitis and ruptured or perforated bladder. [Open Vet J 2024; 14(9.000): 2463-2474]